Cereal protein—potential health benefits as functional foods - Sahin, Oya Irmak; Dundar, Ayşe Neslihan; Sarıcaoğlu, Furkan Turker (Elsevier, 2024)
Cereal proteins are the most balanced plant-based protein source with essential amino acids and are available at low prices. Despite, in some cases, the cereal protein itself being an allergen, there is profound scientific evidence indicating the health benefits of whole grains, wheat, barley, oats, rice, millet, rye, sorghum, and corn. In recent studies, it has been proven that proteins and bioactive peptides extracted from cereals have biological properties such as anticancer, antioxidant, anti-inflammatory, anti-diabetic, and lipid metabolism. This chapter aims to provide an overview of current knowledge on cereal proteins and peptides as functional foods and their potential health benefits. © 2025 Elsevier Inc. All rights reserved.
Keywords: bioactivity; biological substances; biomolecules; Cereal; cereal peptide; cereal protein; functional; health benefits; peptides; protein